UNLEASHING INNOVATION THROUGH EFFECTIVE TALENT MANAGEMENT: A COMPARATIVE ANALYSIS OF STRATEGIES AND PRACTICES IN DIVERSE INDUSTRIAL - Muhamad Rizal Firdaus; Eko Sakapurnama (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research discusses the urgency of talent management in four industrial sectors: technology, health, education, and manufacturing. The main objective is to understand how each sector faces the challenges of attracting, developing and retaining quality talent and the impact on company performance. Qualitative methods were used with in-depth interviews with HR managers and executives in each sector. The research results show that each sector has unique needs and challenges. The technology industry is facing stiff competition for talent with high technical skills and is adopting innovative approaches to recruitment. The health sector emphasizes the importance of scholarships and training programs to overcome the shortage of qualified medical personnel, especially in remote areas. Educational institutions focus on professional development and competitive compensation to attract and retain quality faculty. Meanwhile, the manufacturing sector prioritizes training programs and collaboration with vocational schools to develop technical and managerial skills. Effective talent management strategies have proven important in improving company performance in all sectors studied. This research suggests that companies need to adapt talent management strategies according to their respective industry contexts to maximize organizational competitiveness and success in dynamic global markets.